Deficiencies and Potentialities in business careers of a university in the southeast of Mexico in its distance system (Revista de Investigaciones Universidad del Quindío, 2022)
Higher education institutions are under a new panorama that exceeds what they are used to in terms of virtuality, although many already had platforms where they carried out their school activities, it is worth emphasizing that this way is already a bit obsolete. Emerging technologies give a new versatility to which various institutions choose to delve into them to not only be updated but also to offer a better educational practice by teachers towards students. The following investigation is of a descriptive documentary type, in which diverse theory is collected in relation to the research topic for its analysis and creation of new knowledge, the investigation sought to generate knowledge applicable to the current structure of business careers offered at a university in the Southeast Mexico in order to improve both the teaching practice and the learning experience of the students. Among the applicable strategies, it was found that the generation of digital skills such as the generation of digital capital from the beginning of the degree to not only have a better educational experience but also to face the labor field that requires a deep digital immersion for various aspects that it requires. the labor market and be competitive without being pushed aside by the digital divide.
Keywords: Virtual Classroom; Distance Education; Digital Capital; Digital Competences